Medical Image Computing and Computer Assisted Intervention - MICCAI 2023 26th International Conference, Vancouver, BC, Canada, October 8-12, 2023, Proceedings, Part I - Greenspan, Hayit; Madabhushi, Anant; Mousavi, Parvin; Salcudean, Septimiu; Duncan, James; Syeda-Mahmood, Tanveer; Taylor, Russell (Cham : Springer Nature Switzerland : Imprint: Springer, 2023)
The ten-volume set LNCS 14220, 14221, 14222, 14223, 14224, 14225, 14226, 14227, 14228, and 14229 constitutes the refereed proceedings of the 26th International Conference on Medical Image Computing and Computer-Assisted Intervention, MICCAI 2023, which was held in Vancouver, Canada, in October 2023. The 730 revised full papers presented were carefully reviewed and selected from a total of 2250 submissions. The papers are organized in the following topical sections: Part I: Machine learning with limited supervision and machine learning - transfer learning; Part II: Machine learning - learning strategies; machine learning - explainability, bias, and uncertainty; Part III: Machine learning - explainability, bias and uncertainty; image segmentation; Part IV: Image segmentation; Part V: Computer-aided diagnosis; Part VI: Computer-aided diagnosis; computational pathology; Part VII: Clinical applications - abdomen; clinical applications - breast; clinical applications - cardiac; clinical applications - dermatology; clinical applications - fetal imaging; clinical applications - lung; clinical applications - musculoskeletal; clinical applications - oncology; clinical applications - ophthalmology; clinical applications - vascular; Part VIII: Clinical applications - neuroimaging; microscopy; Part IX: Image-guided intervention, surgical planning, and data science; Part X: Image reconstruction and image registration.
Keywords: Image processing -- Digital techniques; Computer vision; Application software; Machine learning; Education -- Data processing; Social sciences -- Data processing; Biomedical engineering; Computer Imaging, Vision, Pattern Recognition and Graphics; Computer and Information Systems Applications; Machine Learning; Computers and Education; Computer Application in Social and Behavioral Sciences; Biomedical Engineering and Bioengineering